Soil matrix affects the determination of p-nitrophenol and the estimation of β-glucosidase, arylsulfatase, and acid phosphatase activities in subtropical soils - da Silva, Alexandre Bertoldo; Kaschuk, Glaciela (Pedobiologia, 2025)
Increased soil enzyme activity is an indicator of excellent soil health. The activities of soil β-glucosidase, arylsulfatase, and acid phosphatase are determined by quantifying p-nitrophenol, the product of degradation of p-nitrophenyl substrates during soil incubation. However, some p-nitrophenol may adsorb to the soil matrix, leading to underestimations of soil enzyme activities. This study aimed to verify the effects of soil matrices on p-nitrophenol determination and to evaluate their consequences on enzyme activity estimations. Soil samples were collected from 18 locations in the Plateau and Coastal regions of Paraná, Southern Brazil, covering various land uses and subjected to physical and chemical characterization. Three 500 mg soil aliquots from each composite sample per site were incubated following standard procedures. Three calibration curves were then applied: 1) Multiple Point External Standard, with six p-nitrophenol concentrations; 2) Multiple Point Standard Addition, with the same six p-nitrophenol concentrations plus soil; and 3) Single-Point Standard Addition, with a median p-nitrophenol concentration plus soil. Significant differences in the slope coefficients of the linear regressions between the Multiple Point External Standard curve and the Multiple Point Standard Addition curve were attributed to soil matrix effects, resulting in lower enzyme activity estimates. Principal Component Analysis indicated that the soil matrix effect was associated with fine-textured soils high in organic matter. Enzyme activities estimated using the Multiple Point Standard Addition curve did not differ from those obtained with the Single-Point Standard Addition curve, suggesting that both methods are suitable for correcting soil matrix effects. Despite this, results from the first two calibration curves were highly correlated (β-glucosidase, r = 0.8357; acid phosphatase, r = 0.9779; and arylsulfatase, r = 0.9962), suggesting that the soil matrix effect does not significantly impact the interpretation of soil enzyme activity values in soil health assessments. •β-glucosidase and arylsulfatase activities were affected by soil organic matter.•Acid phosphatase activity was related to clay content.•Single point standard addition addresses misestimations of p-nitrophenol.